Ultimate Seismic Resistance Capacity for Long Span Lattice Structures under Vertical Ground Motions. (24th September 2013) - Taniguchi, Yoshiya
Abstract : Seismic resistance capacities of frame structures have been discussed with equilibrium of energies among many researchers. The early one is the limit design presented by Housner, 1956; that is, frame structures should possess the plastic deformation ability equivalent to an earthquake input energy given by a velocity response spectrum. On such studies of response estimation by the energy equilibrium, the potential energy has been generally abandoned, since the effect of self-weight or fixed loads on the potential energy is negligible, while ordinary buildings usually sway in the horizontal direction. However, it could be said that the effect of gravity has to be considered for long span structures since the mass might be concerned with the vertical response. In this paper, as for ultimate seismic resistance capacity of long span structures, an estimation method considering the potential energy is discussed as for plane lattice beams and double-layer cylindrical lattice roofs. The method presented can be done with the information of static nonlinear behavior, natural periods, and velocity response spectrum of seismic motions; that is, any complicated nonlinear time history analysis is not required. The value estimated can be modified with the properties of strain energy absorption and the safety static factor.